0673 Multimodal MRI Reveals Alterations Of Sensorimotor Circuits In Restless Legs Syndrome. (12th April 2019) - Stefani, Ambra; Mitterling, Thomas; Heidbreder, Anna; Steiger, Ruth; Kremser, Christian; Frauscher, Birgit; Gizewski, Elke; Poewe, Werner; Högl, Birgit; Scherfler, Christoph
Abstract: Introduction: Integrated information on brain microstructural integrity and iron storage and its impact on the morphometric profile is not available in restless legs syndrome (RLS). We applied multimodal MRI including diffusion tensor imaging, the transverse relaxation rate (R2*), a marker for iron storage, as well as grey and white matter volume measures to characterize RLS related MRI signal distribution patterns and to analyze their associations with clinical parameters. Methods: Eighty-seven patients with RLS (mean age 51, range 20-72, years; disease duration, mean 13 years, range 1-46 years, of those untreated n=30) and 87 healthy control subjects, individually matched for age and gender, were investigated with multimodal 3T-MRI. Results: Volume of the white matter compartment adjacent to the post and precentral cortex and fractional anisotropy of the frontopontine tract were both significantly reduced in RLS compared to healthy controls, and these alterations were associated with disease duration (r=0.25, p=0.025 and r=0.23, p=0.037, respectively). Corresponding, grey matter volume increases of the right primary motor cortex in RLS (p<0.001), were negatively correlated with the right fractional anisotropy signal of the frontopontine tract (r= -0.22; p<0.05). Iron content evaluated with R2* was reduced in the putamen as well as in temporal and occipital compartments of the RLS cohort compared to the control group (p<0.01). Conclusion: Multimodal MRI identified progressing white matter decline of key somatosensory circuits that may underlie the perception of sensory leg discomfort. Increases of grey matter volume of the premotor cortex is likely to be a consequence of functional neuronal reorganization. Support (If Any): The study was funded by a Grant from Translational Research Fund of the government of Tyrol, Austria, to Birgit Högl and in-kind resources of the Medical University of Innsbruck.